Real world data on the demographic and clinicopathological profile and management of patients with early-stage HER2-positive breast cancer and residual disease treated with adjuvant trastuzumab emtansine (KARMA study) - Silvia Antolín Novoa; Santiago Escrivá-de-Romaní; Pablo Tolosa Ortega; Lucía Oliva Fernández; Rafael López López; Ana López González; Pilar de la Morena Barrio; Isabel Echavarria Díaz-Guardamino; José Enrique Alés Martinez; Zita Garate; Lucia González-Cortijo (Cancer Treatment and Research Communications, 2023)
Introduction: Trastuzumab emtansine (T-DM1) significantly improves invasive disease-free survival and reduces the risk of recurrence in patients with HER2-positive early breast cancer (EBC) with residual disease (RD). The KARMA study aimed to describe the characteristics and management of these patients in clinical practice in Spain. Material and methods: We conducted a multicentre retrospective study in patients with HER2-positive EBC with RD following neoadjuvant treatment (NeoT) and who had received ≥1 dose of T-DM1 as adjuvant treatment. The primary endpoint was the evaluation of sociodemographic and clinicopathological characteristics of these patients. Results: A total of 114 patients were included (March–July 2020). At diagnosis, most tumours were infiltrating ductal carcinoma (IDC) (93.9 %), grade 2 (56.1 %), and hormone receptor (HR)-positive (79.8 %). Over 75 % of patients had disease in operable clinical stages (T1–3 N0–1). In the neoadjuvant setting, 86.8 % of patients received trastuzumab plus pertuzumab, and 23.6 % achieved radiological complete response. Breast-conserving surgery was performed in 55.8 % of patients. Surgical specimens showed that 89.5 % of patients had IDC, 49.1 % grade 2, 84.1 % HR-positive, and 8.3 % HER2-negative disease. Most patients had RD classified as RCB-II and Miller/Payne grade 3/4. Grade 3 treatment-related adverse events (trAEs) occurred in 5.3 % of patients. No grade 4/5 AEs occurred. Over 95 % of patients were free of invasive-disease during T-DM1 adjuvant treatment. Conclusion: The KARMA study describes the characteristics of patients with HER2-positive EBC with RD after NeoT and the real-life management of a T-DM1 adjuvant regimen, which showed a manageable safety profile in line with the KATHERINE trial data.